PENGARUH POSISI LONGITUDINAL DAN RADIAL IRATAN BAMBU PETUNG TERHADAP SIFAT KAYU LAPIS DENGAN INTI KAYU SENGON - , ARIF DHARMA RAFKE; , Prof. Ir. T.A. Prayitno, M.For., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bamboo has been used widely in the community. One species of bamboo which commonly used in Indonesia is petung bamboo. Some of petung bamboo utilization in the community are furniture and crafts. Utilization of petung bamboo for furniture and crafts can not be separated from the value of its natural aesthetic beauty. However, the natural aesthetic beauty of bamboo in its products is not optimal and does not have a high added value because of limitation on shape and dimension of bamboo culm. To solve this problem, bamboo can be processed with lamination technology so it can have a thickness, width, and length dimension as board. In this study, the application of lamination technology in bamboo is made as plywood overlay with petung bamboo thin strip as face and sengon wood as core. This study used a model of a completely randomized experimental design with two factors and three replications, there were factor of longitudinal position of bamboo thin strip (P: base, T: middle, and U: tip) and factor of radial position of bamboo thin strip (d: inner, t: middle, and k: outer). The result of variance analysis that showed a significant different was tested with Tukey Honestly Significant Difference at level test 1% and 5%. Plywood testing in its physical and mechanical properties included moisture content, density, swelling, shrinkage, bonding strength, and wood failure based on ASTM standards and immersion delamination test based on JAS standards. The result of this study shows that the interaction of longitudinal and radial position petung bamboo thin strip gives a very real significant effect on the delamination of surface area and significant effect on the width shrinkage. The combination of petung bamboo thin strip Tip-Outer (Uk) gives the lowest value of the delamination of surface area is 0.216% and the lowest value of width shrinkage is 0.112%. In factor of longitudinal position of bamboo thin strip, from base to the tip, the value of length, width, and thickness swelling, length and thickness shrinkage, delamination of linear length decrease. In factor of radial position of bamboo thin strip, from inner to outer, the value of density, length shrinkage, delamination of linear length, bonding strength, and percentage of wood failure decrease.